2019
DOI: 10.1097/pas.0000000000001272
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of the Prognostic Value of Desmoplastic Reaction Categorization in Stage II Colorectal Cancer

Abstract: Highly accurate risk assessment of recurrence may improve adjuvant treatment practice in stage II colorectal cancer (CRC), which lacks definite prognostic factors. Recent studies indicate the importance of stroma in determining cancer behavior, although there are few histopathologic criteria for its evaluation. A pathology review of 679 stage II CRC patients (1980-2005) was conducted at an institution. Desmoplastic reaction (DR) results were classified as mature, intermediate, or immature depending on the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 25 publications
7
57
0
Order By: Relevance
“…49 On the other hand, our previous retrospective multicentre study found that DR categorisation stratified risk of recurrence for two independent cohorts over a wider range in stage II CRC patients; specifically, the cumulative recurrence rate 5 years after surgery ranged between 9-31% in the first cohort and 11-37% in the second cohort. 23 Given that these figures are similar to those presented here, where there is also a clear differentiation in the recurrence rates among the three prognostic groups (8%, 21% and 32% for Mature, Intermediate and Immature, respectively), it is worth revisiting the classic and H&E-oriented surgical pathology when new treatment-deciding factors based on the role of cancer microenvironment emerge. These may include tumour budding 26 and DR pattern, which could improve upon current genetic staging in terms of cost-benefit performance.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…49 On the other hand, our previous retrospective multicentre study found that DR categorisation stratified risk of recurrence for two independent cohorts over a wider range in stage II CRC patients; specifically, the cumulative recurrence rate 5 years after surgery ranged between 9-31% in the first cohort and 11-37% in the second cohort. 23 Given that these figures are similar to those presented here, where there is also a clear differentiation in the recurrence rates among the three prognostic groups (8%, 21% and 32% for Mature, Intermediate and Immature, respectively), it is worth revisiting the classic and H&E-oriented surgical pathology when new treatment-deciding factors based on the role of cancer microenvironment emerge. These may include tumour budding 26 and DR pattern, which could improve upon current genetic staging in terms of cost-benefit performance.…”
Section: Discussionsupporting
confidence: 80%
“…Recent retrospective multicentre studies revealed that the type of DR in a primary tumour affects postoperative prognostic outcomes independently of tumour stage, and this factor may outweigh conventional tumour factors in terms of the power for predicting RFS in early CRC. 19,23,33 These results were validated in this study, in which DR characterisation was prospectively determined in stage II colon cancer and its prognostic value was evaluated employing three different statistical approaches. First, based on the Cox proportional-hazard model, DR characterisation was identified as an independent prognostic factor, along with Tstage and tumour budding.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…HE-stained slides of resection specimens of early OTSCC were used for the assessment of all stromal features in this study. We categorized desmoplastic reaction based on the maturity of stroma as recently described [11,14] into three groups:…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the desmoplastic reaction, the stroma has been categorized into mature, intermediate, and immature based on morphology and arrangement of collagen and the myxoid nature of stroma. [14]. Of note, the clinical significance of the desmoplastic reaction has not been studied in early OTSCC.…”
Section: Introductionmentioning
confidence: 99%